“There is always a waitlist”: The experiences of perinatal women randomized to a waitlist condition in a trial evaluating a novel online self-directed intervention for perinatal anxiety - Kristjanson, Amanda J.; Hardman, Madison P.; Penner, Kailey E.; Gornik, Megan E.; Pryor, Teaghan A. M.; Petty, Sarah K.; Alcolado, Gillian M.; Furer, Patricia; Reynolds, Kristin A. (Frontiers in Health Services, 2022)
Background: Pregnant and postpartum women are at a heightened risk for the development or worsening of mental health problems, with elevated rates of mood and anxiety disorders noted across studies. Timely access to mental health supports is critical during the perinatal period (spanning pregnancy to one year postpartum), to mitigate potential negative impacts on mother and child. In general adult populations, a small body of research has highlighted the association between being waitlisted for mental health services with a deterioration in mental health. Given the influx of changes experienced in the perinatal period, this population may face unique challenges around being waitlisted. There is a lack of research exploring the experiences of perinatal women waitlisted for psychological services. The current study seeks to understand the experiences of perinatal women randomized to the waitlist condition of a randomized controlled trial. Methods: N = 20 participants (4 pregnant, 16 postpartum) from Canada who were enrolled in a novel online self-directed intervention for perinatal anxiety completed a virtual qualitative interview concerning their experience during the six-week waitlist period for this randomized controlled trial. Interviews were audio-recorded, transcribed, and analyzed according to reflexive thematic analysis. Results: Seven main themes were identified, depicting the waitlist experiences of perinatal participants: a) “There is always a waitlist” (sub-themes: service availability, need to seek support pre-emptively); b) Timing of support access is vital during the perinatal period (sub-themes: prenatal, postpartum); c) Responses to being waitlisted (sub-themes: disappointment, neutral, relief, “there’s probably somebody that needs it more than I do”); d) Identification of helpful supports during the waitlist period (sub-themes: formal supports, informal supports); e) Connections with research team (sub-themes: communication, resource provision); f) Impact of waitlist experience on desire to start program (sub-themes: excitement, “out of sight, out of mind”, nervousness); and g) Improving the waitlist experience (sub-themes: communication, resource provision, triaging). Discussion: Findings highlight the need for timely access to mental health supports during the perinatal period and offer several recommendations for improving the waitlist experience, including providing more frequent waitlist status updates, providing more direct access to intermediate interventions, and triaging patients based on clinical need.